Surfactant usage in nitrile rubber film development through metal plate dipping process - Hui Lai Yong; Munusamy Yamuna; Mohd Ismail Nor Ismaliza; Xian Ooi Zhong; Muniyadi Mathialagan; Jiang Lim Chaw (E3S Web of Conferences)
Developing rubber film in the lab is important for studying the mechanical changes on gloves with different developed formulation. The process in the lab differs from the factory, as the rubber film is formed from dipping a metal plate into the compounded mixture, while the factory uses a well-crafted former to make their gloves in a controlled environment. One issue arises during preparation rubber film in laboratory is the coagulant was unable to uniformly coat the metal plate, which result in producing uneven rubber films. Thus, this work focuses on the incorporation of surfactant into the coagulant solution (Ca(NO3)2) to allow a uniform coating. Two concentrations of two types of surfactants are tested by measuring the contact angle of coagulant to the metal plate. 0.5% of Wetpol 800 surfactant provides an even coating of rubber film on the metal plate after dipping through visual inspection compared to the Ca(NO3)2 alone. The rubber film formed has an average thickness of 0.065 mm, tensile strength of 22.348 MPa, ultimate elongation 1388.4 %, modulus E100 and E300 of 1.377 and 0.731 respectively.